Personal Laws of Religious Communities in India - Master, Meher K (Journal of Dharma, 1986)
The first Prime Minister of India late Pandit Jawaharlal Nehru had a vision of a united nation of India. With the background of the present land-mass of the subcontinent of India carved up between the Royal Princely States, and the Imperial Powers of Europe, his vision of a National Unified State of India was indeed a bold dream. The complexities of the legal variations existing in India were formidable. The majority of the population followed. various beliefs of the Hindu faith. These variations included the Sikhs, Jains, Sindhis as well as Orthodox Hindus who were themselves sub-divided into various sects such as the Krishnaites, Vaishnavites, Shivites as well as many castes and sub-castes each having their own customs, having the force of Personal Law. In addition there waa the large minority community of Muslims also divided. into various groups such as the followers of H. H. the Aga-Kharž, the Vada Mulla of the Dawoodi Vohras, and. the Shias and. Sunnis amongst others. Then came the three minority communities of the Christians, Parsis and Jews. Amongts the Christians there was the sharp division between the Roman Catholics who according to Church Law did not accept the concept of a Civil-Law-Divorce and. the numerous sects of Protestants ; of which the Church of England predcminated as it received. the official support of the British Raj. Upto the time of the independence of India, it was extremely difficult for two persons belonging to different religious communities and governed by different Personal Laws to get married. in India. The old Special Marriage Act provided that where two persons did not believe in any religion and made a declaration to that effect, so that the Personal Law of no religious community would be applicable to them, then they could. avail of the special provisions of this Act and contract a Civil Marriage. The other method open to such persons was for one of the two persons to be converted to the religion of the other and so the same Personal Law would, become applicable to both of them and the marriage would then be solemnised under the Common personal Law. Late Pandit Nehru's own daughter our late beloved Prime Minister Indira Gandhi was faced with this problem directly when she desired to be married to late Mr. Firoze Gandhi. Since conversion is not permitted in the Zoroastrian religion and neither party wanted to declare themselves atheists, the only recourse was for Mr. Gandhi to convert to the Hindu Faith and then have the marriage ceremony solemnised according to Hindu religious customs.